Propostas de educação inclusiva dos institutos federais do Estado do Rio Grande do Sul: alguns apontamentos - Breitenbach, Fabiane Vanessa (2012)
This dissertation was aimed to understand the proposals of inclusive education in the guiding documents of the Federal Institutes of Education, Science and Technology of the State of Rio Grande do Sul (RS) and, in this scenario, how are addressed the people considered, today, the target audience of Special Education. From the critical approach, was conducted Content Analysis (Bardin, 2008; Franco, 2005) of documents produced by the three Federal Institutes of RS: Institutional Development Plans, Institutional Pedagogical Projects and the Statutes. Were also reviewed other documents and information contained on the websites of the institutes. On the assessment and discussion of the data, it was found that while there is a national policy that addresses inclusive education, there is no unity in the actions of the Federal Institutes to propose inclusive education in a cohesive and aligned way between them, because the three institutions studied propose initiatives differently, although all are allocated in the same state of the federation. The existence of an Advisory/Directorship of Inclusive Actions and the (not) place that it occupy in the guiding documents of the institutes do not provide guarantees of effective practices to ensure inclusive education. Therefore, we conclude that the absence of a national policy infers the absence of an institutional policy, since each of the Institutes implements, differently, the reservation of vacancies and/or quotas, ranging from the absence, as is the case of IFRS, passing on reservation of 50% for students graduating from public schools in IFSul, until the selection almost entirely of reservation of vacancies and/or quotas in IFFarroupilha.